Actualization of Religious Moderation Values In Islamic Religious Education Teachers In Madrasah - Magdalena Magdalena; Asnah Asnah; Bestari Endayana (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Religious Moderation is one of the Strategic Programs of the Ministry of Religion which is reduced from the 2020-2024 National Medium-Term Development Plan (RPJMN). The Religious Moderation Program was released by the Ministry of Religion to be implemented in all areas of life, including education. Moreover, one of the authorities of the Ministry of Religion is related to religious and religious education. This is the basis for grounding the idea of Religious Moderation in religious and religious education in formal and informal educational institutions. The application of the values of religious moderation is the main key to realizing them. This assumption is based on the empirical conditions of educators in Padangsidimpuan City. Based on this analytical study of educators, there is a need for a Manual for Strengthening Religious Moderation for educators. In addition, this book is needed especially for Islamic Religious Education teachers who are considered to be a solution in increasing the level of knowledge, understanding, and application of the values of religious moderation both in learning Islamic Religious Education and in the context of life in madrasas and Islamic boarding schools. While it is known that the area around Padangsidimpuan City is a mountainous area which is relatively difficult to access online sources of information, even though this book is provided in electronic or digital form. Therefore, not many educators know and can access this book.